Analysis Of Sharia Aspects In The Digitalization Of Halal Tourism Business : Case Study Of Telaga Warna Wonosobo Pt. Alam Indah - Akbar, Firman Muhammad Abdurrohman; Said, Muhammad; Zahra, Inas Afifah (CV ODIS, 2023)
The digitalization of the halal tourism business has become a major focus in supporting the economic growth and progress of the halal industry. In this context, this study aims to analyze the sharia aspects related to the digitalization of the halal tourism business through a case study of PT Alam Indah located in Telaga Warna, Wonosobo. The research method used is qualitative with a descriptive analytical field and literature approach. The data used in this study were obtained through interviews, observations, and documentation with the Marketing Manager of PT Alam Indah. The results showed that PT Alam Indah has achieved a high level of compliance with the guidelines for organizing tourism based on Sharia principles set out in Fatwa No. 108/DSN-MUI/X/2016. They provide tour packages, destinations and accommodations that are in accordance with Sharia principles, and use Sharia Bank accounts to manage company funds independently. Nonetheless, there is still the use of conventional financial institution services that have not fully adopted sharia principles. In addition, PT Alam Indah has successfully developed its business through effective digitalization. By implementing a digital system since its inception, it can continue to survive and develop in a more advanced and trusted manner. The application owned by PT Alam Indah has fulfilled Sharia principles, by offering halal products without any elements of fraud, Gharar, and with guarantees of security, honesty, professionalism, and providing benefits to users. Overall, the digitalization of the halal tourism business carried out by PT Alam Indah is in line with the established Sharia principles. This research provides a deeper understanding of how sharia aspects are applied in the digitalization of the halal tourism business. The results of this study are expected to contribute to broadening the understanding of business practices that meet Sharia principles in the context of halal tourism. In addition, this research also provides insight into the importance of effective digitalization development in supporting the sustainable growth of halal tourism.